Justifikasi Moral Konvensional atas Prinsip Proporsionalitas dan Penerapannya pada Perusakan Rumah Sakit Al Shifa di Gaza Utara - Raden Roro Friska Sita Arifah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
In general, attacks on hospitals are prohibited under international humanitarian law (IHL), which aims to protect the life and health of civilians during armed conflicts. However, in certain circumstances, hospitals may lose their protection and thus become legitimate targets in warfare if they are considered to be involved in military activities or supporting the parties to the conflict. This brings into question the application of the principle of proportionality, which is an essential element of IHL. The principle of proportionality seeks to balance military necessity with the protection of civilians, requiring that the harm caused by military operations should not be disproportionate to the military advantage sought. This principle demands that military operations be conducted carefully to minimize harm to civilians and civilian objects, including hospitals. However, its application raises significant ethical questions regarding the moral justification of such actions, especially when hospitals are targeted in attacks. One prominent example that raises ethical concerns about this justification is the destruction of Al-Shifa Hospital in Northern Gaza. The hospital was destroyed in an airstrike during the conflict, causing severe harm to the civilian population that relied on this facility. While the principle of proportionality is designed to limit damage, attacks on hospitals such as Al-Shifa raise questions about whether the actions taken were truly consistent with this principle, particularly when the military gain achieved does not seem to outweigh the damage caused to human life and vital infrastructure. This article aims to explore the conventional moral justification of the principle of proportionality in international humanitarian law and evaluate its application in the case of Al-Shifa Hospital, challenging the boundaries of the principle in practice.